Phenotypic and functional testing of circulating regulatory T cells in advanced melanoma patients treated with neoadjuvant ipilimumab. Issue 1 (December 2016) - Retseck, Janet; VanderWeele, Robert; Lin, Hui-Min; Lin, Yan; Butterfield, Lisa; Tarhini, Ahmad
Abstract Background We have previously investigated neoadjuvant ipilimumab (ipi) for patients with locally/regionally advanced melanoma. That initial assessment of peripheral blood mononuclear cells (PBMC) showed a significant increase in shared tumor associated antigen specific CD4+ and CD8+ T cell activation. We also observed a transient increase in circulating T regulatory cells (Treg) with a parallel increase in total CD4+ T cells, as well as a significant decrease in circulating myeloid derived suppressor cells (MDSC). The increase in circulating Treg frequency, as assessed at 6 weeks after initiation of ipilimumab, was significantly associated with improved progression free survival (PFS, p  = 0.034; HR = 0.57) and returned to baseline levels by 12 weeks. To shed light on the unexpected positive correlation between increased Treg and PFS, we here investigated the suppressive activity of circulating Treg at baseline and 6 weeks. Methods Patients were treated with ipi (10 mg/kg intravenously every 3 weeks for 2 doses) bracketing definitive surgery. Treg (CD4+ CD25+ CD127dim/- ) were isolated from pre-ipi (baseline) and post-ipi (6 weeks) PBMC samples. Treg were co-cultured with autologous responder CD4+ T cells that were stimulated with OKT3/IL-2/CD28 and CFSE-labeled T cells. 1:1, 1:2, and 1:5 ratios were tested. Flow cytometery was used to evaluate the degree of Treg proliferation suppression. Results Thirty-five patients were enrolled in the study; 18 patients had adequate PBMC samples with sufficient Treg isolated for Treg functional analysis. At 6 weeks following ipi, a decrease in percent of maximal inhibition of Th by Treg compared to baseline was seen for some patients. Scatter plot analysis showed no association between Treg frequency and function at any ratio or between circulating Treg frequency and function at baseline and at 6 weeks post-ipi. An increase in Treg suppressive function was significantly associated with a decrease in PFS (p  = 0.02). Conclusions We find that Treg frequency measures do not correlate with suppressive activity measured ex vivo. Treg suppressive activity increases correlate with poorer patient outcomes.